1981
DOI: 10.1111/j.1651-2227.1981.tb05545.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Severity of Abo Haemolytic Disease of the Newborn by Cord Blood Tests

Abstract: Seventy-one ABO incompatible (heterospecific) infants and 71 controls, who were free from other potential causes of jaundice, were studied to ascertain which cord blood tests reliably predict the severity of ABO haemolytic disease of the newborn (ABO HDN). The modified Direct Antiglobulin Test (spin DAGT) was positive in all infants who required treatment for haemolytic jaundice and only DAGT positive children showed evidence of impending haemolytic anaemia or compensated haemolysis in cord or capillary blood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…14 Whyte J and Graham observed that the cord blood bilirubin was not diagnostic of haemolytic disease, but it correctly predicted on peak bilirubin levels. 15 In our study, among 110 infants with ABO HDFN, 66.4% had low (risk) bilirubin levels and 33.6% had high (risk) bilirubin levels. History of neonatal jaundice in siblings and severity of disease in ABO HDFN were significantly associated with a higher risk of high bilirubin levels.…”
Section: Parametersmentioning
confidence: 49%
“…14 Whyte J and Graham observed that the cord blood bilirubin was not diagnostic of haemolytic disease, but it correctly predicted on peak bilirubin levels. 15 In our study, among 110 infants with ABO HDFN, 66.4% had low (risk) bilirubin levels and 33.6% had high (risk) bilirubin levels. History of neonatal jaundice in siblings and severity of disease in ABO HDFN were significantly associated with a higher risk of high bilirubin levels.…”
Section: Parametersmentioning
confidence: 49%
“…21 Whyte et al observed that direct antiglobulin test was positive in all infants who required treatment for haemolytic jaundice and only DAT positive children showed evidence of haemolysis in cord or capillary blood. 26 In a study by Rosenfield and Ohno, haemoglobin concentration was slightly lower and bilirubin concentration was slightly higher in ABO incompatible infants as compared to ABO compatible infants, while haemoglobin concentration was distinctly lower and bilirubin concentration was distinctly higher among 14% of DAT positive ABO incompatible infants in comparison with a negative antiglobulin test group.…”
Section: Discussionmentioning
confidence: 93%
“…DAT positive children showed evidence of impending haemolytic anaemia or compensated haemolysis in cord or capillary blood, while elution test had no predictive value. 26 David et al and Quinn et al observed that DAT was neither diagnostic nor predictive of severity in ABO HDFN. 27,20 Density of A and B antigens in cord red cells was studied using an immuno-enzymatic assay and no statistically significant association was found between antigen maturity and severity of ABO HDFN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clinical course and severity of subsequent hyperbilirubinaemia or isommune disease is diffi cult to predict in a newborn with ABO incompa bility because there is no single test that is of high predic ve value 15,16 .…”
Section: Discussionmentioning
confidence: 99%